Pengaruh Kompetensi, Motivasi Budaya Organisasional Kinerja Dosen Dimediasi Kepuasan Kerja Pada “ MMTC” Yogyakarta - Supardi Supardi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This research is about the influence of competence, motivation and organizational culture on lecturer performance mediated by job satisfaction at "MMTC" Yogyakarta High School. This research needs to be done because performance is a picture of organizational success, not merely the results achieved, also the processes that a person or organization undertakes to achieve its goals. So it is necessary to know how much influence and the direction of the relationship of several factors on the influence of employee performance in an organization, namely competence, motivation, and organizational culture factors that affect lecturer performance through job satisfaction at the "MMTC" Yogyakarta High School, so that it can be input, suggestion and alternative. in human resource management and policy development in improving existing human resource management, especially lecturer performance so that they are ready to compete and excel in their field of study. The subjects of this research are permanent lecturers at the "MMTC" Yogyakarta High School. The results showed that the hypothesis proposed was appropriate to explain that competence, motivation, and organizational culture had a positive and significant effect on the performance of lecturers at "MMTC" Yogyakarta High School. Other results show that competence, motivation, and organizational culture through job satisfaction have a positive and significant effect on the performance of lecturers at "MMTC" Yogyakarta High School.